2014
DOI: 10.1080/00032719.2014.886693
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Interactions withRicinus communisAgglutinins Studied by Biolayer Interferometry

Abstract: Two related agglutinins are present in the seeds of Ricinus communis (castor): ricin, a dichain ribosome-inactivating protein and Ricinus communis agglutinin-1, a much less toxic tetrameric hemagglutinin. The immunochemical analysis of these agglutinins is of special interest because ricin toxicity has resulted in both accidental and intentional poisonings, while it has also provided a potential cancer chemotherapeutic in the form of an immunoconjugate. We previously characterized a panel of monoclonal antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Although the study of thermal stability indicated that IgY was more stable than mouse polyclonal Ab at 65°, mouse mAbs used in many of our studies shared the high thermal stability of IgY (e.g. mAbs 1443 and 1797; Brandon, Adams, et al, 2014). IgY could be especially useful when a large quantity of PBS pAb is required, but it remains to be seen whether other features of IgY, such as its altered hinge region, afford advantages in sensor methodology.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although the study of thermal stability indicated that IgY was more stable than mouse polyclonal Ab at 65°, mouse mAbs used in many of our studies shared the high thermal stability of IgY (e.g. mAbs 1443 and 1797; Brandon, Adams, et al, 2014). IgY could be especially useful when a large quantity of PBS pAb is required, but it remains to be seen whether other features of IgY, such as its altered hinge region, afford advantages in sensor methodology.…”
Section: Discussionmentioning
confidence: 89%
“…These assays were conducted at neutral pH at ambient temperature (about 20°). However, we also used the mAbs in an optical sensor system and found that mAb 1642 was too acidlabile to permit regeneration using 10 s pulses with 10 mM glycine-HCl, pH 1.7 (Brandon, Adams, Yang, & Korn, 2014). We hypothesize that the same structural features than confer acid lability also render mAb 1642 heat-labile.…”
Section: Stability Of Antibodiesmentioning
confidence: 97%
“…Asialofetuin was obtained from Sigma (St. Louis, MO). The principal buffers and milk samples used in ELISAs and BLI were phosphate-buffered saline (PBS), PBS–0.05% (v/v) Tween-20 (PBST), and PBST with 10 mg/mL bovine serum albumin (BSA), and 0.01% (w/v) thimerosal (BPT). , For binding in the BLI system, both PBS and kinetics buffer (KB, PBST with 1 mg/mL BSA) were used at pH 7.4. Biotinylated mAbs were detected with horseradish peroxidase (HRP)–streptavidin (SA) conjugate (Invitrogen, Eugene, OR) at 0.3–1 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The immunochemistry of ricin has been extensively studied, particularly to optimize therapeutic immunotoxins containing ricin A chain and to define potentially protective and therapeutic antibodies . Exploitation of ricin antibodies and the amplification afforded by the polymerase chain reaction (PCR) has contributed new tools for food defense. , In an earlier study, we used BLI to study the interaction of ricin and RCA-1 with antibodies . In this report, we describe BLI and ELISA experiments to quantitate milk matrix effects and mitigate their impact on the analysis of a carbohydrate-binding protein, such as ricin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation